Effect of Bird Yaw/Pitch Angles on Soft Impact Damage of a Fan Assembly. (16th January 2021) - Li, Junjie; Lou, Yunfeng; Yu, Gaoyuan; Li, Tong; Jin, Xianlong
Abstract : This paper presents a numerical investigation of bird attitude angles affecting the soft-impact damage of a full fan assembly. Firstly, considering the geometry of a mallard, a real bird model is established by the Smoothed Particle Hydrodynamics (SPH) method and calibrated with available test data. Then, complying with airworthiness requirements, simulations of a full-bladed fan assembly subjected to a real bird were conducted to determine the critical ingestion parameters (CIP). Furthermore, a real bird with different attitude angles aimed at a full fan assembly was simulated. Results show that attitude angles of the bird produce a significant impact on the effect of the bird strike on rotating blades and would increase the possibility of blade failures, especially for the yaw angle of -45° and the pitch angle of −60°. It is invaluable for commercial airlines and engine manufactures to provide safe flight and landing by adopting the real bird model with critical yaw and pitch angles in the design for resistance to bird ingestion.